An Unsolved Dilemma: Contracted vs. In-House Guarding - Tiszolczi, Balázs Gergely (Magyar Rendészet, 2023)
There are questions in the field of physical security that are hard to answer. One such existing dilemma is whether to choose contracted or in-house guarding. Deploying security officers is a must in almost every security system to appropriately handle system-related risks, so most security managers meet this problem during their careers. Since there is no “one size fits all” solution to this problem, in this article, various points of view are shown to help security professionals decide between the two types of service when the question is on the table.